Understanding symmetrical components for power system modeling - Das, J. C., 1934- (IEEE Press series on power engineering, 2017)
An essential guide to studying symmetrical component theory This book utilizes symmetrical components for analyzing unbalanced three-phase electrical systems, by applying single-phase analysis tools. The author covers two approaches for studying symmetrical components; the physical approach, avoiding many mathematical matrix algebra equations, and a mathematical approach, using matrix theory. Divided into seven sections, topics include: symmetrical components using matrix methods, fundamental concepts of symmetrical components, symmetrical component s ¿́¿transmission lines and cables, sequence components of rotating equipment and static load, three-phase models of transformers and conductors, unsymmetrical fault calculations, and some limitations of symmetrical components. In addition, this book: . Provides concise treatment of symmetrical components. Describes major sequence models of power system components. Discusses Electromagnetic Transient Program (EMTP) models. Includes worked examples to illustrate the complexity of calculations, followed by matrix methods of solution which have been adopted for calculations on digital computers.